GENDER BASED ANALYSIS ON ACTIVITIES OF Parkia biglobosa (Jacq) G. Don AND Vitelleria paradoxa (C. F. Gaertn) VALUE CHAINS IN DERIVED SAVANNAH ZONE OF NIGERIA (FUDMA JOURNAL OF SCIENCES, 2021)
The research examined the gender based activities on Parkia biglobosa and Vitelleria paradoxa value chains in derived savannah zone of Nigeria using Oyo State as a case study. The research survey design was adopted which involved administration of semi-structured questionnaires of one hundred and twenty (120) respondents in two Local Government areas of Oyo State namely: Atisbo and Saki. The study areas were purposively selected based on the abundance of the selected Non Timber Forest Products (NTFPs). The data were analysed using descriptive statistic. The result showed that farm had the highest number of seeds for collection (48.3% and 41.7%) of Parkia biglobosa and Vitelleria paradoxa followed by community forests. Greater percentage of the population of Shea butter and Parkia producers in the study area were dominated by aged group which were mostly women. Produce were mainly for local consumption while a few numbers attract the larger domestic and international markets. Therefore, it is recommended that government should help in providing simple, easy technology that will facilitate good hygiene practices, packaging and also provide basic infrastructures like boreholes, sorting, cracking, dehuller and milling machines for both the fruits and seeds processors
Keywords: Gender Analysis, Parkia biglobosa, Vitelleria paradoxa, Value chain, Derived savanna